INNOVATION ACTIVITY IN EDUCATIONAL AND METHODIC ASSOCIATION OF RUSSIAN UNIVERSITIES FOR AVIATION DIRECTIONS AND SPECIALTIES - Yu. M. Chinyuchin; N. Y. Bambaeva; A. S. Borzova (Научный вестник МГТУ ГА, 2016)
In this article the historical background for establishment of educational and methodic association of universities in aviation dimension and specialities are described, results of its activity shown and further development of educational operation is proposed.